Microbiological analysis of dental plaque in children with Down syndrome - R. S. Nazarian; O. V. Iskorostenska; T. N. Zamazіy (Zaporozhye State Medical University, 2017)
Topical focus of modern dentistry is improving the prevention of dental diseases in children with Down syndrome. The goal of this work is to assess the species composition of the microflora of dental plaque in children with Down syndrome in comparison with conditionally healthy children. Materials and methods. In this work we have used the results of bacteriological research of clinical material of 10 children with Down syndrome and 15 conditionally healthy children. Swabs from cervical part of the teeth have been taken with the help of a sterile disposable tampon. Microbiological research has included a discharge of microorganisms, identification by morphological, cultural and biochemical properties of cultures. The research has been conducted on clinical strains of microorganisms discharged from dental plaque in children with Down syndrome and conditionally healthy children. The results. In the investigated material of children with Down syndrome, we have detected gram-positive microorganisms, such as Streptococcus spp with α-hemolytic activity, Bacillus spp and Candida fungi, as well as gram-negative bacteria: E. aerogenes, K. pneumoniae, P. aeruginosa, Neisseria spp (Table 1). In the microflora of dental plaque, facultative anaerobic microorganisms have been discharged more often than aerobes. Conclusions. In control and main group, dental plaque microflora is more often presented by associations of bacteria and Candida fungi. The discharge rate of Streptococcus spp with α-hemolytic activity and Candida albicans is equal in both groups. Nonpathogenic Neisseria species have been presented in 9.1 % of strains in the main group, whereas in the control group there have been 35 % of strains. In children with Down syndrome we have detected gram-negative bacilli - enterobacteria with a density of microbial colonization of E. aerogenes Ig (4.66 ± 0.6) cfu/g, pseudomonads and gram-positive spore-forming bacilli - Ig (5.0 ± 0.0) cfu/g, which are representatives of the allochthonous (transitory, fickle) microflora of the oral cavity. Their long stay in the oral cavity prevents the effect of nonspecific protective factors, as well as antagonistic activity of autochthonous microflora. In case of some disorders of physiological state, representatives of allochthonous microflora can linger in the oral cavity, multiply and cause pathological processes.